Development of an electronic publication for children "Alphabet for children" - Жук, Екатерина Юрьевна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of existing multimedia products is given, the process of designing and developing an information structure, exterior design of the electronic publication, as well as the creation of navigation is described. The choice of colors and fonts, software is proved